Pengaruh penggunaan spin card yoga terhadap motivasi ibu hamil untuk melakukan yoga mandiri - Ratih Kumorojati; Alfie Ardiana Sari; Dian Puspitasari; Nur Rahmawati Sholihah (MEDIA ILMU KESEHATAN, 2021)
Background: The care provided by midwives to reduce discomfort is by teaching Yoga to pregnant women a safe physical exercise for mother and fetus, yoga is usually done every day that trains the mother's breathing, physical and psychological, the implementation of Yoga in pregnant women must be accompanied by a facilitator who competent. During the COVID-19 pandemic, pregnant women have difficulty doing yoga in health facilities. In overcoming these obstacles, independent yoga media is needed that is safe for pregnant women, the media can be in the form of videos, flashcards, and spin cards as well as practical and easy-to-use yoga movement pictures as a guide.Objective: The purpose of this study was to determine the effectiveness of using Spin Card Yoga on the motivation of pregnant women to carry out independent yoga.Methods: This type of research is a quasi-experimental research with one group pre-test-post-test design. This research was conducted by giving a pretest (initial observation) in the form of a questionnaire before being given an intervention. After that the intervention was given, then a posttest (final observation) in the form of a questionnaire was also carried out (Hidayat, 2007). The population in this study was 30 pregnant women living in the working area of the Asih Waluyojati clinic. The sampling technique used is the convenience sampling technique (nonprobability). The sample in this study was 25 people. data analysis using the Wilcoxon test.Results: The majority of mothers' motivation in participating in yoga before being given spin cards yoga in the less category (76.19%), while after being given spin cards yoga intervention, the majority of respondents' motivation was in the high category as much as 75%. Based on the pairwise comparison test using Wilcoxon , the value of P = 0.001 was obtained. This value means P<0.05, which means that there is an effect of using spin cards on the motivation of pregnant women to do yoga.Conclusion: Based on the discussion that has been described, it can be concluded that the majority of motivation before using spin cards yoga is less (76.19%), the majority of motivation after using spin cards yoga is high (75%), and the use of spin cards yoga affects the increase in motivation of pregnant women to do yoga independently.